Validation of a Kazakhstani Version of the Mental Health Continuum—Short Form - Hernández-Torrano, Daniel; Ibrayeva, Laura; Muratkyzy, Ainur; Lim, Natalya; Nurtayev, Yerden; Almukhambetova, Ainur; Clementi, Alessandra; Sparks, Jason (Frontiers in Psychology, 2021)
Positive mental health and well-being are significant dimensions of health, employment, and educational outcomes. Research on positive mental health and well-being requires measurement instruments in native languages for use in local contexts and target populations. This study examines the psychometric properties of the Kazakhstani version of the Mental Health Continuum - Short Form (MHC-SF), a brief self-report instrument measuring emotional, social, and psychological well-being. The sample included 664 university students (425 females) purposefully selected in three higher education institutions in South, East, and Central Kazakhstan. Their average age was 20.25 and ranged from 18 to 43. Participants completed a Kazakhstani version of the MHC-SF online. Statistical analyses to evaluate the structural validity, reliability, and measurement invariance of the Kazakhstani version of the MHC-SF were performed. The results confirmed the superiority of the bifactor model (i.e., three separated factors of well-being plus a general factor of well-being) over the alternatives. However, most of the reliable variance was attributable to the general well-being factor. Subscale scores were unreliable, explaining very low variance beyond that explained by the general factor. The findings demonstrated the measurement invariance of the MHC-SF across gender and age. Overall, these findings support the use of the Kazakhstani version of the MHC-SF to examine a general factor of well-being and the measurement invariance of the instrument across gender and age groups. However, the results advise against the interpretation of the subscale scores as unequivocal indicators of emotional, social, and psychological well-being.